2019
DOI: 10.1111/cei.13250
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone effects on heterochromatin: the role of kinase signaling

Abstract: Epigenetic effects of anti-psychotic medications are poorly understood. We have appropriated a model whereby heterochromatin is established through 24-or 48-h lipopolysaccharide (LPS) treatment, and tested the epigenetic effects of risperidone along the adenylyl cyclase/protein kinase A (AC/PKA) pathway in human liposarcoma cells that express the LPSsensitive Toll-like receptor (TLR)-4. Human SW872 cells were cultured with LPS and mRNA expression levels and epigenetic modifications of dimethylated lysine 9 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…S3 and S4) indicate that these genes are still regulated by heterochromatin despite exhibiting weaker heterochromatin association compared to those in broadly heterochromatin forming CGI − genes (i.e., within cHet domains). This is supported by prior studies demonstrating that local heterochromatin formation within euchromatic domains can suppress expression of surrounding genes [e.g., “local heterochromatin” ( 50 ), “restricted heterochromatin” ( 51 ), or “focal heterochromatin” ( 52 , 53 )] and that up-regulated CGI − genes located within euchromatic domains, such as inflammatory genes Tnf and Il6 , are regulated by heterochromatin formation ( 54 , 55 ). Our counterintuitive observation also explains, at least in part, why heterochromatin decondensation during aging has not been clearly linked with gene expression changes in prior studies ( 56 , 57 ).…”
Section: Discussionsupporting
confidence: 67%
“…S3 and S4) indicate that these genes are still regulated by heterochromatin despite exhibiting weaker heterochromatin association compared to those in broadly heterochromatin forming CGI − genes (i.e., within cHet domains). This is supported by prior studies demonstrating that local heterochromatin formation within euchromatic domains can suppress expression of surrounding genes [e.g., “local heterochromatin” ( 50 ), “restricted heterochromatin” ( 51 ), or “focal heterochromatin” ( 52 , 53 )] and that up-regulated CGI − genes located within euchromatic domains, such as inflammatory genes Tnf and Il6 , are regulated by heterochromatin formation ( 54 , 55 ). Our counterintuitive observation also explains, at least in part, why heterochromatin decondensation during aging has not been clearly linked with gene expression changes in prior studies ( 56 , 57 ).…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, our non-significant mRNA expression results may be a result of the variable antipsychotic dosing present in our sample. We have also shown that antipsychotic treatment in vitro can decrease heterochromatin levels and increase promoter phosphorylation and mRNA expression of genes that are tolerized (heterochromatinized) via an endotoxin tolerance paradigm, while other promoters do not respond in this way (36,60). This targeted response to antipsychotic treatment could be 10.3389/fpsyt.2022.1006109 an explanation for the LIPJ and NRGN genes that did not show coordination with their H3K9me2 promoter occupation levels.…”
Section: Heterochromatin Regulation Of Catalytic Activitymentioning
confidence: 89%
“…Our findings suggest that alternate/parallel signaling pathways capable of targeting genomic heterochromatin may provide a supplemental advantage. Considering this approach, we have elsewhere demonstrated that signaling along the kinase pathways in cell cultures can target heterochromatin assemblies by regulating histone phosphorylation (36). Because heterochromatin is a stable modification and in equilibrium with its regulatory factors, its measurement along specific gene networks in the neuron would allow a reverse engineering approach to study "what stress" deposits heterochromatin on "which network."…”
Section: Conclusion and Summarymentioning
confidence: 99%
“…While CPZE calculated for the participants treated with oral antipsychotics did not differ between illness duration groups, it may be that long-term antipsychotic treatment contributes to shifts in immune signatures in participants with schizophrenia with cumulative effects over the course of illness. Indeed, we have previously shown that antipsychotics can influence the assembly of promoter chromatin and increase immune gene expression (68,69).…”
Section: Discussionmentioning
confidence: 99%